2011
DOI: 10.1007/s11661-011-0905-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Combined Addition of Cu and Aluminum Oxide Nanoparticles on Mechanical Properties and Microstructure of Al-7Si-0.3Mg Alloy

Abstract: In this study, an ultrasonic cavitation based dispersion technique was used to fabricate Al-7Si-0.3Mg alloyed with Cu and reinforced with 1 wt pct Al 2 O 3 nanoparticles, in order to investigate their influence on the mechanical properties and microstructures of Al-7Si-0.3Mg alloy. The combined addition of 0.5 pct Cu with 1 pct Al 2 O 3 nanoparticles increased the yield strength, tensile strength, and ductility of the as-cast Al-7Si-0.3Mg alloy, mostly due to grain refinement and modification of the eutectic S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 23 publications
0
41
1
Order By: Relevance
“…[11][12][13] Although there are a number of available fabrication routes for MMNCs, an ultrasonic method, [5,14] which combines casting with ultrasonic cavitation-based dispersion of nanoparticles in molten alloys, seems an economical and promising route in terms of producing engineering components with complex shapes. [7,15] In the fabrication of MMNCs by liquid state routes, poor wettability (which can affect the bonding at the reinforcement-matrix interface) and the tendency of ceramic nanoparticles to agglomerate and cluster due to their large surface-to-volume ratio are the main barriers to obtaining a uniform dispersion of nanoparticles into the matrix. [5] However, it has been shown that good dispersion of ceramic nanoparticles in molten metals is possible with the ultrasonic method due to high intensity ultrasonic waves with localized implosive impact, namely transient cavitation, and acoustic streaming.…”
Section: Metal Matrix Nanocomposites (Mmncs)mentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Although there are a number of available fabrication routes for MMNCs, an ultrasonic method, [5,14] which combines casting with ultrasonic cavitation-based dispersion of nanoparticles in molten alloys, seems an economical and promising route in terms of producing engineering components with complex shapes. [7,15] In the fabrication of MMNCs by liquid state routes, poor wettability (which can affect the bonding at the reinforcement-matrix interface) and the tendency of ceramic nanoparticles to agglomerate and cluster due to their large surface-to-volume ratio are the main barriers to obtaining a uniform dispersion of nanoparticles into the matrix. [5] However, it has been shown that good dispersion of ceramic nanoparticles in molten metals is possible with the ultrasonic method due to high intensity ultrasonic waves with localized implosive impact, namely transient cavitation, and acoustic streaming.…”
Section: Metal Matrix Nanocomposites (Mmncs)mentioning
confidence: 99%
“…[5] However, it has been shown that good dispersion of ceramic nanoparticles in molten metals is possible with the ultrasonic method due to high intensity ultrasonic waves with localized implosive impact, namely transient cavitation, and acoustic streaming. [15][16][17] It has been assumed that ultrasonic cavitation could break up nanoparticle clusters due to the collapse of cavitation bubbles when they reach a critical size in the clusters. [18] Acoustic streaming which is a circulating flow is then considered to play a role for distributing nanoparticles throughout the matrix.…”
Section: Metal Matrix Nanocomposites (Mmncs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional fabrication methods, such as high-energy ball milling, electroplating, and sputtering, cannot be used for this purpose without significant post-processing [1][2][3][4][5]. More recently, there have been several processing technologies available to fabricate these MMNCs, such as powder metallurgy [6], severe plastic deformation [7,8], friction stir processing [9], and solidification processing (liquid infiltration [10,11], disintegrated melt deposition [12], spray atomization [13], and ultrasonic-cavitation based technique [14][15][16]). Of these processing methods, the solidification processing is a highly adaptable and cost-effective method to produce large volume of near-netshape MMNCs with complex features in bulk for various industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…This problem can be solved using the impact of external fields on liquid metals which leads to de-agglomeration of nanoparticles and their homogeneous distribution in the melt volume and ingot structure as a result. Ultrasonic treatment is one of the most efficient ways of melt treatment leading to alloy grain size reduction and homogeneous distribution of reinforcing particles in its structure [4,5]. Besides, ultrasonic treatment intensifies degassing process, provides additional mixing, prevents coring and concentration of non-metal inclusions on grain boundaries, which has a positive impact of the formation of uniform metal structure in the process of solidification [6].…”
Section: Introductionmentioning
confidence: 99%